O ambiente de trabalho no setor bancário e o bem-estar - Lucena, Cynthia Suennia Damasceno (2005)
Wich the big transformations at the world of labor, thus as the appearing of the negatives psicologicals consequencies? Publications in books and articles about the health of the workers have been seen in the last 40 years, pointing at the increase of occupational ills, increase of the absenteeism, reach the redation between the labor and the family. With the appearing of the neoliberal sistem, changed all the net of relations, thus as the temporary labor contract, the flexibility at the work timetable, and others, that privilege the capitalism, in detriment of the worker health. It was given emphasis to the banking worker, in time that the banks and the banking agencies were one of the departaments that more suffered the impact of the productive restructuring at the last years. 200 bank clerks shared the search, in that 41,9% was female and 58,1% was male, 60,9% presenting a civil state married, following of 28,4% of single. The participants answered the following instruments: Scale of Positives and Negative Kindness, General Health Questionaire GHQ 12, Scale of Organization, Conditions and Labor Relations, Scale of Desire (own authorship), Scale about economic situation and a social-demographic record car. With the objective of trying the instruments of measure, it was checking the psychometric parameter of the search scales. We could verify that it has been more positive than negative ones for the mental health, but it was found some kind of depression and unsatisfied with their lives in some pieces of the sample. We can finally say that the work place has an impact at the mental health of the bank clerks. So, some interventions actions to promote the worker health could be essential